2013
DOI: 10.1159/000355520
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Primary Oral Health Care Approach in the Dental Curriculum: A Tanzanian Experience

Abstract: This paper is based on a conference presentation made during the inauguration of the Faculty of Dentistry, Kuwait University, as a World Health Organization Collaborating Centre for Primary Oral Health Care (POHC) on November 27-28, 2012. The aim of this paper is to review how the POHC approach has been integrated into the dental curriculum, sharing the Tanzanian experience as a case presentation from a developing country. The burden of oral diseases worldwide is high, and the current oral health workforce is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Similar to our findings, a lack of provider capacity, training and experience for operating in the context of cross-disciplinary or integrated settings is another challenge considered in the literature (22,23). It is also suggested that integration of the PHC approach into the dental curriculum is crucial for training a competent workforce (29). Given this situation, there is a need to provide the current and future PHC and dental workforce with the skills needed to practice integrated oral health services (23,30).…”
Section: Discussionsupporting
confidence: 72%
“…Similar to our findings, a lack of provider capacity, training and experience for operating in the context of cross-disciplinary or integrated settings is another challenge considered in the literature (22,23). It is also suggested that integration of the PHC approach into the dental curriculum is crucial for training a competent workforce (29). Given this situation, there is a need to provide the current and future PHC and dental workforce with the skills needed to practice integrated oral health services (23,30).…”
Section: Discussionsupporting
confidence: 72%
“…It should not only equip the graduates with the knowledge, skills, attitudes and behaviour but also should accommodate the culture and social principles acceptable to the community they serve for achieving the best outcome. [28] Nurses and midwives provide health services in all levels of health facilities. Nurses can play a pivotal role in expanding access to overall health care for the population.…”
Section: Nursing Training and Oral Health Care In Tanzaniamentioning
confidence: 99%
“…For example, as new diseases continue to emerge, the development of new technology, treatment equipment requires continuing education and professional development. [28] While we are implementing this curriculum for training nursing in Tanzania, there is a great step made towards bridging the oral health disparities in low income countries by infusing this oral curriculum into existing curricula of the training institution. [29] Similarly, oral health training for nurses in Tanzania will be strategically implemented and infused into the existing curricula in order to promote effectiveness and sustainability.…”
Section: Projections On How the Pilot Will Improve Oral Health In Tanmentioning
confidence: 99%
“…Initiatives introduced in other parts of the world such as the United States, Canada and Poland, in preparing their medical graduates with roles in oral health maintenance, have seen a dynamic shift in the conduct and delivery of medical education towards a learning environment that promotes holistic patient care (17)(18)(19)(20)(21)(22)(23)(24)(25). The evolving trend in medical education seeks institutional commitment to accommodate curricular changes to comply with the global quality and standard of teaching and learning as well as the future practice of medicine (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%